Epileptic syndromes in children with cerebral palsy - T. T. Batysheva; A. N. Platonova; O. V. Bykova (Эпилепсия и пароксизмальные состояния, 2016)
Modern data of frequency and structure of epilepsy in children with cerebral palsy were analyzed. Basic unfavorable prognostic factors of epilepsy development were formulated. Worsening prognosis of motor and cognitive development of children with cerebral palsy, epileptic seizures limit volume of their rehabilitation. Early prediction of epilepsy development risk in cerebral palsy children is extremely important link in the treatment choice procedure